Mechanical Assessment of the Risk of Atherosclerotic Plaque Rupture in Carotid Arteries with a Focus on Damage Accumulation - GHASEMI, MILAD (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2019)
Carotid atherosclerotic plaque rupture is one of the leading causes of death. Growth and development of atherosclerotic plaque alters the geometry and mechanical environment of the healthy arterial tissue. Supra-physiological stress values can occur in regions around the plaque shoulders in atherosclerotic plaques. Surgical interventions such as stenting or endarterectomy can also induce large loads on the arterial wall. To assess the risk of atherosclerotic plaque rupture in carotid arteries, in this thesis, a constituent specific study was first performed to investigate the role of collagenous and non-collagenous tissue in the response of arterial walls to supra-physiological loads. A structural constitutive model was also developed to capture the mechanical behaviour of non-collagenous and collagenous tissue under physiological and supra-physiological loading conditions. Observing the important role of collagen fibres in damage relevant phenomena, the orientation of collagen fibres in healthy and diseased carotid bifurcations was studied in the next step. Collagen fibres can re-orient in biological tissues to maximize the load bearing capacity of their underlying structure. In this thesis, an optimum distribution of collagen fibres was predicted in both healthy and diseased carotid bifurcations. A novel remodelling metric was also introduced to characterize the lack of remodelling in terms of re-orientation in the atherosclerotic plaques which weakens the arterial tissue and may increase the risk of plaque rupture. To accurately capture the mechanical behaviour of the arterial tissue, constitutive laws require accurate material properties. Different forms of mechanical tests can be conducted to calibrate these material models. However, using constitutive models to accurately assess the risk of atherosclerotic plaque rupture requires patient specific material parameters. To address this limitation, a geometrical metric was introduced and systematically assessed in the final study of this thesis. The high-risk areas predicted using this remodelling metric were compared with regions at highest stress values and areas where the maximum damage was accumulated in the collagen fibres within the arterial wall. Such geometrical metrics can be used independently, or in parallel with other indicators of risk of atherosclerotic plaque rupture to more efficiently and accurately assess the vulnerability of plaques in carotid arteries.
APPROVED